Utility of teleconsultation in accessing eye care in a developing country during COVID-19 pandemic. - Hassan Mansoor; Saad Alam Khan; Tayyab Afghani; Muhammad Zaman Assir; Mahmood Ali; Wajid Ali Khan (PLoS ONE)
Objective To evaluate the utility of teleconsultation in the provision of eye care services during the COVID-19 lockdown. Disparities in the consultation burden of sub-specialities and socio-demographic differences in teleconsultation utilization were also assessed. Methods Al-Shifa Trust Eye Hospital Rawalpindi began audio and video teleconsultation using broadband telecommunication services during the lockdown. Patients' and consultations' data gathered during the first three weeks after the commencement of this programme were compared with data from the four weeks prior to lockdown. The weekly consultation ratio and overall consultation burden of sub-specialities were measured. Chi-Square tests of association determined the relationship between different variables (socioeconomic status and consultation characteristics) and consultation modality (on-site vs online). Results In total, 17507 on-site consultations (4377/week) were conducted compared to 1431 teleconsultations (477/week), which maintained 10.89% of the weekly pre-lockdown eye care services. The post-lockdown teleconsultation programme saw a relatively higher percentage of service utility among female (47.09% vs 44.71%), younger-age (31.33±19.45 vs 41.25±23.32 years) and higher-socioeconomic-status (32.21% vs 0.30%) patients compared to pre-lockdown on-site consultations. The most common indication for teleconsultation was red-eye (16.70%). While cornea and glaucoma clinics maintained most of the pre-lockdown services (30.42% and 29% respectively), the highest dropout was seen in optometric and vitreoretinal services supporting only 5.54% and 8.28% of pre-lockdown services, respectively. Conclusion Digital initiatives could partially maintain eye care services during the lockdown. Focused strategies to improve teleconsultation utilization are required during the pandemic and beyond.